Desenvolvimento de um sistema de medição em tempo real, por espectroscopia de bioimpedância, capaz de determinar a concentração celular - Silva, Marcos Antonio Salvino da (2020)
This work developed an alternative biomass measurement system applied for real-time monitoring (online) of bioprocesses, through bioimpedance spectroscopy, using the BIS-STEP technique. The construction of this work was carried out in two stages: the first, to test the feasibility of applying this bioprocess monitoring technique, the experiments were carried out with the commercial yeast Saccharomyces cerevisiae. In this step, use a linear regression multivariate (LRM) to estimate the total number of total and viable cells, using bioimpedance parameters. The second step, in the interest of Farmanguinhos/Fiocruz, to extrapolate this technique to bacteria Bacillus thuringiensis var. israelensis (Bti). The latter (Bti) presented greater difficulty in the direct application of LRM commonly used in dielectric spectroscopy or bioimpedance techniques. A solution found, using respiratory parameters - oxygen uptake rate (OUR), shows the most comprehensive ones and can also be applied to the data obtained from the first experiments. The statiscal results were satisfactory for both microorganisms with an average Pearson correlation coefficient (r) above 0.9 and the Bland-Altman model evaluated the agreement between analytical and bioimpedance methods.